Ekspor-Impor dan Dampaknya terhadap Pertumbuhan Ekonomi di Indonesia - Setiawati, Ririt Iriani Sri; Islamudin, Ardhi (Jurnal Bisnis Indonesia, 2024)
This study examines the investigation of how the global economy affects the domestic economy. Theinternational economy includes the export and import of products between nations. This study uses adescriptive methodology and a literature review to evaluate how the state of the global economy hasimpacted Indonesia's GDP growth, as measured by exports and imports, using a qualitativetechnique. According to the findings of the descriptive analysis and literature review, exports have afavorable effect on economic growth, which implies that as the value of exports rises, so will the rateof economic expansion. On the other side, imports have a negative effect on economic growth, whichmeans that the slower the expansion, the higher the value of imports.Keywords: Export; Import; Economic Growth; GDP